Theology-Science: Monitoring the Dichotomy of Science and Religion in the Era 5.0 Mehdi Gholshani's Perspective - Salamuddin Salamuddin (Postgraduate, University of Mataram, 2023)
This paper aims to see the extent of the problems faced by humans, especially educators in overseeing the Religion-Science dichotomy. Here the researcher uses Mehdi Golshani's thinking. This is because Gholsani is one of the modern physicists who offers